Effect of Different Polymerization Degrees and Fatty Acids of Polyglycerol Esters on the Physical Properties and Whippability of Recombined Dairy Cream - Guosen Yan; Shiran Wang; Yang Li; Jing Zhang; Hao Ding; Yan Li; Liebing Zhang (Foods, 2022)
Polyglycerol esters (PGEs) are used as emulsifiers in recombined dairy cream (RDC) to improve product quality. In this study, the effects of four PGEs with different polymerization degrees and esterification on the particle size, viscosity, zeta potential, and microrheology of RDC emulsions were investigated, and the whipping time, overrun, serum loss, and firmness of the RDC emulsions were recorded. The results show that the addition of the PGEs reduced the particle size (from 2.75 μm to 1.48–1.73 μm) and increased the viscosity (from 41.92 cP to 73.50–100 cP) and stability (from 0.354 to 0.105–0.128), which were related to the change in interfacial properties and the weakening of Brownian motion, but there were differences in the effect on the whipping behavior of the RDCs. Although the addition of 0.9% triglyceride monolaurate gave the emulsion the best stability, the RDC had a longer whipping time (318 s) and a lower overrun (116.6%). Comparatively, the 0.7–0.9% concentrations of PGE55 and tripolycerol monostearate (TMS) provided RDC with good stability and aeration characteristics, allowing inflation within 100 s and expansion rates of up to 218.24% and 186.88%, respectively. In addition, the higher degree of polymerization of polyglyceryl-10 monstearate (PMS) did not work well at any concentration. These results contribute to understanding the mechanism of action of PGEs and improving the quality of RDC.